2012
DOI: 10.1002/smll.201201779
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoprisms as Optoacoustic Signal Nanoamplifiers for In Vivo Bioimaging of Gastrointestinal Cancers

Abstract: Early detection of cancer greatly increases the chances of a simpler and more effective treatment. Traditional imaging techniques are often limited by shallow penetration, low sensitivity, low specificity, poor spatial resolution or the use of ionizing radiation. Hybrid modalities, like optoacoustic imaging, an emerging molecular imaging modality, contribute to improving most of these limitations. However, this imaging method is hindered by relatively low signal contrast. Here, gold nanoprisms (AuNPrs) are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 54 publications
0
114
1
Order By: Relevance
“…The surfactant-free methods for synthesis and characterization of functionalized PEGylated AuNprs can be found in our previous publications [7,9]. Briefly, before functionalization, AuNprs were washed in deionized (DI) water and suspended in 2-(morpholino)ethanesulfonic acid (MES; 0.1 M, pH 6.0) solution.…”
Section: Synthesis and Characterization Of Functionalized Pegylated Amentioning
confidence: 99%
See 1 more Smart Citation
“…The surfactant-free methods for synthesis and characterization of functionalized PEGylated AuNprs can be found in our previous publications [7,9]. Briefly, before functionalization, AuNprs were washed in deionized (DI) water and suspended in 2-(morpholino)ethanesulfonic acid (MES; 0.1 M, pH 6.0) solution.…”
Section: Synthesis and Characterization Of Functionalized Pegylated Amentioning
confidence: 99%
“…More recently, Bao et al reported the use of AuNprs as a novel contrast agent for the hybrid technique of photoacoustic imaging (PAI). The authors demonstrated an in silico electron tomographic reconstruction of such Au nanostructures, which showed promise for application in biomedical imaging, drug delivery, and photothermal therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their plasmonic properties, gold nanoparticles (GNPs) have been proposed as advantageous nano-sized materials for use in the various diagnostic and therapeutic applications, such as cell imaging, targeted drug delivery, thermal ablation, phototherapy [1][2][3][4][5][6][7].. To date spherical GNPs have been proven as one of the most biocompatible NP models for biological-based applications [8][9][10][11][12]. Recently, it has been reported that the specific shape of GNPs can be exploited to advantageously tune these nanomaterials for any biomedical application of choice [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the specific shape of GNPs can be exploited to advantageously tune these nanomaterials for any biomedical application of choice [8,13]. Examples of such alternatively shaped GNPs being produced include, amongst others, rods, triangles, hexagons, prisms, urchins, cubes and wires [11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation